Perbandingan Bahasa Indonesia dan Bahasa Melayu Pontianak: Tinjauan Dialektologi (Comparasion between Indonesia Languague and Pontianak Malay Languague: A Dialectological Study) - Bagus Prakoso (Universitas Sebelas Maret, 2026)
This study aims to measure the linguistic distance between Indonesian and Pontianak Malay through a dialectological approach. Indonesian, which is rooted in Malay, has undergone development through processes of standardization, the absorption of foreign vocabulary, and orthographic reform. However, the extent of the linguistic distance between Indonesian and Pontianak Malay has not been discussed in previous studies. This research employs the 200-word Swadesh list. The data were collected using the non-participatory observation method involving three native speakers of Pontianak Malay and were subsequently analyzed using Guiter’s (1974) dialectometric approach. The findings reveal that only 11 lexical items differ, with a percentage of difference below 20%. According to Guiter’s classification, the two varieties do not show significant differences and remain within the same language group. The differences identified are predominantly phonological variations, such as final sound changes and the deletion of certain consonants. These findings confirm that Indonesian and Pontianak Malay maintain a very high degree of linguistic proximity despite undergoing different historical developments.